PENERAPAN PERMAINAN TRADISIONAL DAKON DALAM MENDUKUNG PERKEMBANGAN SOSIAL-EMOSIONAL ANAK USIA 5-6 TAHUN DI RA BAHRUL ULUM - Lestari, Nofita; Endah Wahyu Sugiharti (LPPM IAD Probolinggo, 2025)
In early childhood, the role of educators has a great influence on children's social and emotional development. This is because early childhood tends to imitate what they see, without being able to distinguish between good and bad behavior. Therefore, they easily imitate the attitudes of those around them. One way that can be used to observe a child's social-emotional development is through traditional games such as dakon. The purpose of this study is to find out how the game of dakon can support early childhood social-emotional development. The results of the study show that the dakon game at RA Bahrul Ulum can be an effective medium in training children's social and emotional attitudes in a simpler way. This game helps children understand noble values such as helpfulness, empathy, responsibility for actions taken, and accepting defeat. This research is focused on children aged 5-6 years with the hope of understanding and developing social-emotional attitudes, such as tidying up the game tools after playing dakon, caring for friends who don't understand the rules of the game, and learning to accept defeat with open arms. Keywords: social-emotional development; Early Childhood; Dakon Games.